2011
DOI: 10.1098/rstb.2011.0092
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural defences in animals against pathogens and parasites: parallels with the pillars of medicine in humans

Abstract: No other theme in animal biology seems to be more central than the concept of employing strategies to survive and successfully reproduce. In nature, controlling or avoiding pathogens and parasites is an essential fitness strategy because of the ever-present disease-causing organisms. The diseasecontrol strategies discussed here are: physical avoidance and removal of pathogens and parasites; quarantine or peripheralization of conspecifics that could be carrying potential pathogens; herbal medicine, animal style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
144
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(147 citation statements)
references
References 75 publications
2
144
0
1
Order By: Relevance
“…Some of these anti-parasite strategies may themselves be facilitated by social processes (such as ectoparasite removal during allogrooming) or be socially learned [20]. Comparisons have previously been made between animal self-medication behaviours and human medicine [61], and further study of animal behavioural responses to disease may shed light on the evolution of human medical practices. Additionally, we only investigated one aspect of parasitism; other measures such as prevalence, intensity or virulence of parasites could provide further insights to the hypotheses that we tested [20].…”
Section: (C) Ameliorating the Costs Of Parasitismmentioning
confidence: 99%
“…Some of these anti-parasite strategies may themselves be facilitated by social processes (such as ectoparasite removal during allogrooming) or be socially learned [20]. Comparisons have previously been made between animal self-medication behaviours and human medicine [61], and further study of animal behavioural responses to disease may shed light on the evolution of human medical practices. Additionally, we only investigated one aspect of parasitism; other measures such as prevalence, intensity or virulence of parasites could provide further insights to the hypotheses that we tested [20].…”
Section: (C) Ameliorating the Costs Of Parasitismmentioning
confidence: 99%
“…Indeed, recent research has demonstrated that the first line of defense against infectious disease is located in the nervous system-what has been referred to as the "behavioral immune system" (Schaller & Park, 2011). Like many other animals (Hart, 2011), humans are endowed with a suite of psychological mechanisms that facilitate the detection and avoidance of sources of contaminants, including conspecifics.…”
Section: Introductionmentioning
confidence: 99%
“…Animals have thus developed behavioural strategies to avoid infection [1][2][3], akin to the suite of behaviours we collectively refer to as 'hygiene' among humans [4]. Some well-known behavioural defences against parasites include their direct removal via grooming or weeding [5,6], the avoidance of infected conspecifics [7] and strategies for waste management [8], all of which function to mitigate fitness losses associated with infection.…”
Section: Introductionmentioning
confidence: 99%